An Automated Testing Framework for Cross-Browser Visual Incompatibility Detection - Zhen Xu; James Miller (Universitas Dian Nuswantoro and IndoCEISS, 2018)
Due to the rapid evolution of web applications and computer techniques, visual incompatibility of web pages has become a problem across different browsers and platforms influencing the functionality of the web applications. At the present, researchers have made progress to address such issues; in addition, many commercial tools have emerged as well. However, drawbacks still exist in the existing work, where fully automate testing at the system level is still not achieved. In this paper, we attempt to propose a framework to detect the cross browser visual incompatibilities automatically. Highlights of the proposed framework include template based case organization, version based automation, and similarity embedded incompatibilities identification.